Lignans and Neolignans: Plant secondary metabolites as a reservoir of biologically active substances - Zálešák, František; Bon, David Jean-Yves Denis; Pospíšil, Jiří (Pharmacological research, 2019)
Lignans and neolignans are plant secondary metabolites derived from the oxidative coupling of phenylpropanoids. Biological activity of these phenolic compounds ranges from antioxidant, antitumor (terminaloside P, IC50 = 10 nM), anti-inflammatory, anti-neurodegenerative (schibitubin B, IC50 = 3.2 nM) and antiviral (patentiflorin A, IC50 = 14-23 nM) to antimicrobial. In addition, it was observed that several members of this group, namely enterolactone and its biochemical precursors also known as phytoestrogens, possess important protective properties. Most of these lignans and neolignans are presented in reasonable amounts in one's diet and thus the protection they provide against the colon and breast cancer, to name a few, is even more important to note. Similarly, neuroprotective properties were observed (schisanwilsonin G, IC50 = 3.2 nM) These structural motives also serve as an important starting point in the development of anticancer drugs. Presumably the most famous members of this family, etoposide and teniposide, synthetic derivatives of podophyllotoxin, are used in the clinical treatment of lymphocytic leukemia, certain brain tumors, and lung tumors already for nearly 20 years. This review describes 413 lignans and neolignans which have been isolated between 2016 and mid-2018 being reported in more than 300 peer-reviewed articles. It covers their source, structure elucidation, and bioactivity. Within the review, the structure-based overview of compounds as well as the bioactivity-based overview of compounds are described.
Keywords: sekundární metabolismus; Plants; Lignans; Animals; Humans; lidé; rostliny; zvířata; lignany; Secondary Metabolism